Exploring The Perception of BPBD Apparatus on Disaster Budgeting Using a Phenomenological Approach - Hartati, Noorina; Abdul Halim; Oluwatoyin Muse Johnson Popoola (Riset Akuntansi dan Keuangan Indonesia, 2024)
This phenomenological study explores the perceptions of the Disaster Management Agency (BPBD) officials in Sleman and Bantul districts in planning disaster budgets. Through in-depth face-to-face interviews with four BPBD officials from Sleman and Bantul districts, the study finds that disaster risk assessment plays a significant role in pre-disaster budget allocation, while historical experiences dictate the allocation of funds during and after a disaster. Effective and efficient disaster budgeting in Sleman and Bantul districts requires inter-agency collaboration and a participatory approach involving volunteer communities and the public. The main finding of this study is that budget constraints necessitate alternative sources of funding.